(untitled) (Revista de História da UEG (REVHIST), 2020)
The objective of this work is to analyze the discursive construction of the Sertão / Semiarid in the statements of the acquaintance present in the cordéis and in the music. The sources analyzed were: the cordéis produced by ASA (Articulation of the Semiarid), in the period 2003-2004; the cordéis produced by INSA (National Semiarid Institute), in the period 2008-2011; and the CD “Belo Sertão: The acquaintance with the Semi-arid by means of songs”, which was launched in 2006. It was found that, in opposition to the drought discourse, the statements of coexistence establish a beautiful sertão. This discursive operation makes the semiarid identifiable from images and texts that accentuate the natural beauty and richness of a space; the strength, intelligence and cultural expression of a people. As a political strategy, it is about establishing a new discursive order to anchor looks and interpretations, to serve as a foundation for what is said about the Semiarid, as well as the recognition of its identity. Keywords: Sertão. Semiarid. Acquaintance. Cordel. Music.